Immune checkpoint inhibitor increased mortality in lung cancer patients with Pneumocystis jirovecii pneumonia: a comparative retrospective cohort study - Fan, Bo; Sun, Xiaoyan; Han, Weijie; Zou, Yimin; Chen, Fei; Lan, Fen; Li, Wen; Mao, Yanxiong (Frontiers in Oncology, 2024)
Introduction: Pneumocystis jirovecii pneumonia (PJP) is a life-threatening infection in immunocompromised individuals. Immune checkpoint inhibitor (ICI) has brought significant survival benefit in lung cancer patients. Although the few studies showed there was high mortality in PJP patients with ICI use, these studies had no comparative control groups.Methods: A retrospective study was conducted to compare the mortality in PJP patients with lung cancer between those treated with ICI and a concurrent control group treated without ICI.Results: A total number of 20 non-human immunodeficiency virus (HIV) patients with confirmed PJP and co-existing lung cancer were included in the current study, and classified into ICI group (n=9) and non-ICI group (n=11).There was a clear trend to a shorter onset of PJP in ICI group than non-ICI group (118.9±60.9 vs 253.0±185.1 days), although without statistical significance (p=0.053). Bronchoscopic alveolar lavage fluid were collected from all patients and used to identify Pneumocystispneumocystis jirovecii. In both groups, metagenomics next-generation sequencing (mNGS) were the most used diagnostic techniques. Within 28 days after the onset of PJP, mortality was significantly higher in the ICI group than non-ICI group (33.3% vs 0, p=0.042)Lung cancer patients with ICI use had a higher mortality rate after PJP infection than patients without ICI use. Prospective studies with larger sample size and a multi-center design are warranted to further verify the present results.